Agro-Industries for Development 2009
DOI: 10.1079/9781845935764.0010
|View full text |Cite
|
Sign up to set email alerts
|

Building the political case for agro-industries and agribusiness in developing countries.

Abstract: This chapter characterizes the processes of agro-industrialization in developing countries and builds a political case for agro-industries as a driver of growth and development. The case is developed around two main arguments. One cornerstone of their argument is that rapid changes in agrifood systems are shifting the basis for competitiveness. Increasingly, competitiveness is being determined by factors such as economies of scale, efficiencies in logistics, compliance with stringent grades and standards, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The increase in the demand for agri-food products has also favored the development of agro-industrial enterprises, a phenomenon observed mainly in developing countries. Process of agro-industrialization (Henson and Cranfield, 2009;Maertens and Fabry, 2019) is generated by consumer requirements, technical progress, liberalization of trade in agricultural products (Radulescu and Dumbravescu, 2008;Bojan et al, 2017;Voica and Panait, 2017;Borsellino et al, 2019) or liberalization capital movements (Matei, 2004). The divers framework of economic agents involved in feeding foreign capital flows from the agricultural sector has diversified considerably, in addition to transnational companies making their presence felt and the investment funds and financial institutions that support the food security policy of governments that finance or consider investment in agriculture an opportunity not to be missed given the need to diversify the portfolio to reduce risk (Matei, 2004;UNCTAD, 2009;Panait et al, 2016).Foreign investors have nuanced their way of implantation in the agricultural sector over time, in the sense that in recent decades there has been a trend of land acquisition in developing countries (FDI in land) and less involvement in their activities.…”
Section: Transformation Of Agrifood Sector Under the Influence Of Formentioning
confidence: 99%
“…The increase in the demand for agri-food products has also favored the development of agro-industrial enterprises, a phenomenon observed mainly in developing countries. Process of agro-industrialization (Henson and Cranfield, 2009;Maertens and Fabry, 2019) is generated by consumer requirements, technical progress, liberalization of trade in agricultural products (Radulescu and Dumbravescu, 2008;Bojan et al, 2017;Voica and Panait, 2017;Borsellino et al, 2019) or liberalization capital movements (Matei, 2004). The divers framework of economic agents involved in feeding foreign capital flows from the agricultural sector has diversified considerably, in addition to transnational companies making their presence felt and the investment funds and financial institutions that support the food security policy of governments that finance or consider investment in agriculture an opportunity not to be missed given the need to diversify the portfolio to reduce risk (Matei, 2004;UNCTAD, 2009;Panait et al, 2016).Foreign investors have nuanced their way of implantation in the agricultural sector over time, in the sense that in recent decades there has been a trend of land acquisition in developing countries (FDI in land) and less involvement in their activities.…”
Section: Transformation Of Agrifood Sector Under the Influence Of Formentioning
confidence: 99%
“…In this setting, primary industry serves to add value to raw, unrefined or un-extracted material rather than purvey it to firms in other industries (Carter and Easton, 2011). Primary industry associated with production, processing, distribution and marketing of agricultural productsagroindustry-provides an example in the economies of both developed and developing nations: it has emphasized value addition and challenges ideas of boundaries between primary, secondary and tertiary industries (Reardon and Barrett, 2000;Henson and Cranfield, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The growth of agro industries of developing countries is intensified due to dynamic structural changes, obeying international standards of product and procedures safety and quality, as well as due to technological innovation and a vertical and horizontal integration level increase. Significant factors were also market liberalization and changes within the demand structure in developed countries, resulting in an increase of export as well as increasing competitiveness (Henson, Cranfield, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Agro industry is consisted from sectors which process raw materials of agriculture, fisheries and forestry. It is a part of the agro business complex, which includes suppliers for agriculture, fisheries and forestry as well as distributors of food and non food products of the agro industry (Henson, Cranfield, 2009). …”
Section: Introductionmentioning
confidence: 99%